Biomimetics Bridging the Gap - Haidar, Ziyad S. (Biomedical Engineering, 2023)
Biomimetics is an innovative form of technology that emulates, imitates, or mimics nature in order to improve human lives by creating desirable solutions. It is the study of nature and natural phenomena in an attempt to understand its laws, principles, and underlying mechanisms, to obtain ideas from nature, and to apply concepts that may benefit science, engineering, pharmacy, dentistry, and medicine. Smart/intelligent biomaterials for tissue engineering and regenerative medicine are fine examples of biomimetics. Yet, biomimicry can go above and beyond the simplistic inspiration and use of natural properties as the basis for the innovation of new products. It bridges the gap between the lab and the industry via the intra-disciplinary design and formulation of functional solutions combining knowledge, methods, techniques, and advances in the fields of chemistry, biology, architecture, engineering, medicine, pharmaceutics, dentistry, and biomedical engineering. Three-dimensional printing, self-healing nanocoatings, hydrogels, bio-mechanical carbon nanotubes, stimuli-sensitive and -responsive cell/drug delivery systems, and robotics are some of the topics covered in this book. In a simplified style, the book provides interested readers with a practical reference approaching biomimetics and biomimicry from a realistic and translational perspective, discussing problems and offering solutions and including studies ranging from basics to the clinic to scale-up and industrial or go-to-market obstacles. Through Biomimetics - Bridging the Gap, you'll quickly discover that biomimicry is more than just looking at a silkworm (silk is one of the first examples in history) or at the shape of a flower, a damselfly, or even a humpback whale and becoming re-inspired. Biomimicry is an intra-/multi-disciplinary methodology and technological-oriented approach presently employed by the most innovative organizations on this planet.